A high salt diet protects interleukin 10-deficient mice against chronic colitis by improving the mucosal barrier function. (October 2022) - Wang, Dezhi; Jin, Hua; Sheng, Jianqiu; Cheng, Leon; Lin, Qing; Lazerev, Mark; Jin, Peng; Li, Xuhang
Abstract: A high salt diet (HSD) is often associated with a high risk for a variety of diseases, such as obesity and cardiovascular disease. Previous studies have demonstrated that an HSD enhances Th17 responses and increases the severity of autoimmune diseases. In this study, we investigated the effects of HSD (4% NaCl w/w) on colitis in IL-10 -/- mice by comparing it with IL-10 -/- mice on a normal salt diet (NSD, 1% NaCl w/w). The colonic epithelial barrier integrity in IL-10 -/- mice, as well as differentiated Caco-2 cells exposed to high NaCl and proinflammatory cytokines, was also evaluated. Surprisingly, an HSD significantly ameliorated macroscopic colitis, improved the intestinal permeability of FITC-dextran, and decreased multiple proinflammatory cytokines in the colonic mucosa of IL-10 -/- mice. While occludin and claudin-1, two major tight-junction proteins, were markedly down-regulated in IL-10 -/- mice, HSD effectively restored their expressions. In Caco-2 cells, proinflammatory cytokines (TNF-α and IL-1β) potently decreased the expression of occludin and claudin-1 regardless of salt conditions [0.9% (standard), 1.2%, or 1.5% NaCl]. Under high salt conditions (1.5% NaCl), transepithelial electrical resistance (TEER) was elevated, while the addition of IL-10 further downregulated occludin and claudin-1 expressions by ~50% and lowered TEER. These findings suggest that, in the absence of IL-10, HSD promotes intestinal epithelial integrity and exerts an anti-inflammatory role as demonstrated by alleviated colitis in IL-10 -/- mice. Moreover, Caco-2 data indicate that, in an inflammatory environment and under high NaCl conditions, IL-10 may play a proinflammatory role by disrupting colonic epithelial integrity and thus further promoting inflammation. Highlights: HSD ameliorates macroscopic disease/colitis in IL-10-/- mice. HSD downregulates inflammatory factors in the colonic mucosa of IL-10-/- mice. HSD upregulates occludin and claudin-1 in the colonic mucosa of IL-10-/- mice. High salt increases epithelial barrier function under inflammation without IL-10. IL-10 decreases epithelial barrier function under both high salt and inflammation.